Magnesium phosphate bone cement / nano-enzyme composite material as well as preparation method and application thereof

By preparing a composite of oxygen-vacancy cerium oxide and magnesium phosphate bone cement, the acoustic and dynamic properties and nanozyme activity are enhanced, solving the problem of the lack of antibacterial function in magnesium phosphate bone cement and realizing the application of antibacterial bone repair materials.

CN119488639APending Publication Date: 2025-02-21XIN HUA HOSPITAL AFFILIATED TO SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466550.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Magnesium phosphate bone cement lacks antibacterial properties, limiting its application in the treatment of infected bone defects, and the electron-hole recombination of cerium oxide in sonodynamic therapy further restricts its application.

Method used

A composite of oxygen-vacancy cerium oxide and magnesium phosphate bone cement was prepared to enhance acoustic and dynamic properties through oxygen vacancy defects and to combine with nanozyme activity to prepare a magnesium phosphate bone cement/nanozyme composite material.

Benefits of technology

The material achieves antibacterial properties, promotes cell proliferation, and possesses acoustic-dynamic properties, making it suitable for bone repair and treatment of infected bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488639A_ABST
    Figure CN119488639A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium phosphate bone cement / nano enzyme composite material. The magnesium phosphate bone cement / nano enzyme composite material is prepared from CaHPO4, NaH2PO4, MgO powder, hydroxyapatite and oxygen vacancy cerium oxide. The invention also discloses an application of the magnesium phosphate bone cement / nano-enzyme composite material in preparation of a bone repair scaffold. The oxygen vacancy cerium oxide is prepared, through oxygen vacancy defects, electron-hole recombination is inhibited, separation of the oxygen vacancy cerium oxide is promoted, and the sonodynamic performance of the oxygen vacancy cerium oxide is enhanced. In addition, magnesium phosphate bone cement and oxygen vacancy cerium oxide are prepared into a composite material, and the bone cement is endowed with sonodynamic performance and nano-enzyme activity, so that the bone cement has an antibacterial function, promotes cell proliferation and realizes bone repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and in particular relates to a magnesium phosphate bone cement / nanoenzyme composite material and a preparation method and application thereof. Background Art

[0002] Magnesium phosphate bone cement has good coagulation, mechanical strength and osteogenic properties, and is often used as a bone filling material to repair bone defects. Its excellent degradation performance allows it to provide support for new bone growth, while matching the growth rate of new bone and gradually being replaced by new bone. However, magnesium phosphate bone cement itself does not have antibacterial function, which is limited in the treatment of infected bone defects. Therefore, it needs to be modified.

[0003] Sonodynamic therapy (SDT) is a non-invasive antimicrobial treatment strategy that uses ultrasound (US) to trigger sonosensitizers to undergo redox reactions with water and oxygen in the surrounding environment to produce oxygen. - Various ROS such as ·OH and ·OH cause oxidative damage and death of bacteria and destroy bacterial biofilm. Since SDT has the advantages of deep tissue penetration, little tissue damage, controllability and non-invasiveness, and ROS will not make bacteria resistant, it provides a new way to treat deep tissue infections.

[0004] Nanozymes are nanomaterials with similar enzymatic activities to natural enzymes, and have attracted extensive attention in biomedical fields such as antibacterial and tissue repair. Nanozymes with peroxidase (POD)-like enzyme activity can produce ·OH, kill bacteria, and can be used to treat drug-resistant bacterial infections; while nanozymes with catalase (CAT)-like enzyme activity can remove excess ROS (H2O2) in the diseased area, relieve cell oxidative stress, and avoid excessive inflammatory responses, and can therefore be used to promote tissue repair.

[0005] Cerium oxide (CeO2) is a biocompatible nanozyme with multiple enzyme activities (POD and CAT), which can exert POD-like enzyme activity in acidic environment and CAT-like enzyme activity in neutral environment, and has pH responsiveness. Due to its rapid electron-hole recombination, cerium oxide has poor sonodynamic performance, which limits its application in sonodynamics. Summary of the invention

[0006] The purpose of the invention is to provide a magnesium phosphate bone cement / nanoenzyme composite material.

[0007] Another object of the present invention is to provide a method for preparing the magnesium phosphate bone cement / nanozyme composite material.

[0008] Another object of the present invention is to provide an application of the magnesium phosphate bone cement / nanoenzyme composite material in the preparation of a bone repair scaffold or a bone repair material.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] The first aspect of the present invention provides a magnesium phosphate bone cement / nanozyme composite material, which is made of CaHPO4, NaH2PO4, MgO powder, hydroxyapatite (HA), and oxygen vacancy cerium oxide. The molar ratio of CaHPO4, NaH2PO4 and MgO is 1-4:1-4:1 (preferably 2:2:1), the mass of hydroxyapatite (HA) accounts for 5-20wt% (preferably 10wt%) of the total mass of CaHPO4, NaH2PO4 and MgO, and the mass of oxygen vacancy cerium oxide accounts for 5-40wt% (preferably 10wt%, 20wt%, 30wt%) of the total mass of CaHPO4, NaH2PO4, MgO and hydroxyapatite.

[0011] The oxygen vacancy cerium oxide is prepared from cerium oxide and sodium borohydride in a molar ratio of 1:0.5-2 (preferably 1:0.5, 1:1, 1:2).

[0012] The particle size of the oxygen vacancy cerium oxide is 20 to 100 nm (preferably 50 nm).

[0013] The second aspect of the present invention provides a method for preparing the magnesium phosphate bone cement / nanozyme composite material, comprising the following steps:

[0014] Mix CaHPO4, NaH2PO4 and MgO powders in a molar ratio of 1 to 4:1 to 4:1 (preferably 2:2:1), add hydroxyapatite (HA) and mix evenly, the mass of hydroxyapatite (HA) accounts for 5 to 20wt% (preferably 10wt%) of the total mass of CaHPO4, NaH2PO4 and MgO, mix the above mixed powder evenly with oxygen vacancy cerium oxide, the mass of oxygen vacancy cerium oxide accounts for 5 to 40wt% (preferably 10wt%, 20wt%, 30wt%) of the total mass of CaHPO4, NaH2PO4, MgO and hydroxyapatite, add deionized water so that the liquid-solid ratio is 170 to 210 μL / g (preferably 200 μL / g), fully blend, fill into a mold for molding, and solidify to obtain the magnesium phosphate bone cement / nanozyme composite material.

[0015] The curing conditions are as follows: the sample is placed in an incubator at a temperature of 37° C. and a humidity of 100% for curing for 1 to 72 hours (preferably 72 hours).

[0016] The preparation method of the oxygen vacancy cerium oxide comprises the following steps:

[0017] Cerium oxide and sodium borohydride are mixed in a molar ratio of 1:0.5-2 (preferably 1:0.5, 1:1, 1:2), calcined for 0.5-2h (preferably 1h) in an argon atmosphere at a temperature of 350-500°C (preferably 400°C), washed, and dried to obtain the oxygen vacancy cerium oxide.

[0018] The washing conditions are: washing with water and ethanol in sequence.

[0019] The drying conditions are as follows: drying at 60° C. for 1 h.

[0020] The preparation method of the MgO powder comprises the following steps:

[0021] The basic magnesium carbonate is calcined at a temperature of 750-900° C. (preferably 800° C.) for 0.5-2 h (preferably 1 h) for dehydration, and then calcined at a temperature of 1450-1600° C. (preferably 1550° C.) for 0.5-3 h (preferably 2 h) to obtain a magnesium oxide block, which is then ground to obtain the MgO powder.

[0022] The third aspect of the present invention provides an application of the magnesium phosphate bone cement / nanoenzyme composite material in the preparation of a bone repair scaffold.

[0023] The fourth aspect of the present invention provides a use of the magnesium phosphate bone cement / nanoenzyme composite material in the preparation of bone repair materials or bone transplant materials.

[0024] Due to the adoption of the above technical solution, the present invention has the following advantages and beneficial effects:

[0025] The present invention prepares oxygen vacancy cerium oxide, and through the oxygen vacancy defect, inhibits the recombination of electrons and holes and promotes their separation, thereby enhancing its acoustic dynamic performance. In addition, magnesium phosphate bone cement and oxygen vacancy cerium oxide are prepared into a composite material, which gives the bone cement acoustic dynamic performance and nanoenzyme activity, so that it has antibacterial function and promotes cell proliferation, thereby achieving bone repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of SEM images of bCeO at different magnifications.

[0027] Figure 2 It is a schematic diagram of the XRD pattern of bCeO.

[0028] Figure 3 It is a schematic diagram of the acoustic dynamic performance results of bCeO.

[0029] Figure 4 It is the bandgap width of bCeO, the valence band XPS spectrum of CeO-2, and the schematic diagram of electrochemical impedance spectroscopy.

[0030] Figure 5 It is a schematic diagram of the POD enzyme activity and CAT enzyme activity data results of bCeO.

[0031] Figure 6 It is a schematic diagram of the acoustic dynamic performance results of different samples.

[0032] Figure 7 It is a schematic diagram of the POD enzyme activity and CAT enzyme activity results of different samples.

[0033] Figure 8 This is a schematic diagram of the cytotoxicity and cell proliferation results of different samples.

[0034] Fig. 9 It is a picture of colonies and a schematic diagram of the antibacterial rate results after culturing different samples and under different conditions. DETAILED DESCRIPTION

[0035] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0036] Example 1

[0037] The first step is the preparation of oxygen vacancy cerium oxide (bCeO):

[0038] Cerium oxide (CeO2) (0.006 mol, 1.00 g) and sodium borohydride (NaBH4) (0.003 mol, 0.1099 g) were mixed in a molar ratio of cerium oxide to sodium borohydride of 2:1, and calcined in a tube furnace at 400°C in an argon atmosphere for 1 h. The resulting powder was washed with water and ethanol in turn, and dried (60°C, 1 h) to obtain CeO2 with oxygen vacancies, abbreviated as CeO-1.

[0039] Cerium oxide (CeO2) (0.006 mol, 1.00 g) and sodium borohydride (NaBH4) (0.006 mol, 0.2198 g) were mixed in a molar ratio of cerium oxide to sodium borohydride of 1:1, and calcined in a tube furnace at 400°C in an argon atmosphere for 1 h. The resulting powder was washed with water and ethanol in turn, and dried (60°C, 1 h) to obtain CeO2 with oxygen vacancies, abbreviated as CeO-2.

[0040] Cerium oxide (CeO2) (0.006 mol, 1.00 g) and sodium borohydride (NaBH4) (0.012 mol, 0.4395 g) were mixed in a molar ratio of cerium oxide to sodium borohydride of 1:2, and calcined in a tube furnace at 400°C in an argon atmosphere for 1 h. The resulting powder was washed with water and ethanol in turn, and dried (60°C, 1 h) to obtain CeO2 with oxygen vacancies, abbreviated as CeO-3.

[0041] Table 1b CeO sample grouping

[0042]

[0043] Step 2: Preparation of magnesium phosphate cement (MPC)

[0044] The basic magnesium carbonate was placed in a muffle furnace, calcined at 800°C for 1 hour for dehydration, and then calcined at 1550°C for 2 hours to obtain a magnesium oxide block, which was then ground to obtain magnesium oxide (MgO) powder.

[0045] Calcium hydrogen phosphate (CaHPO4), sodium dihydrogen phosphate (NaH2PO4) and MgO are sieved to obtain CaHPO4, NaH2PO4 and MgO powders with a particle size of less than 75 μm.

[0046] CaHPO4 (0.01 mol, 1.33 g), NaH2PO4 (0.01 mol, 1.17 g) and MgO powder (0.005 mol, 0.20 g) were mixed, and the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1. Hydroxyapatite (HA) (5.38 × 10 -4 mol, 0.27g) were mixed evenly, the mass of hydroxyapatite (HA) accounted for 10wt% of the total mass of CaHPO4, NaH2PO4 and MgO, deionized water was added to the mixed powder so that the liquid-solid ratio was 200μL / g (add 0.59ml of water), and the mixture was fully blended and filled into a polytetrafluoroethylene mold, and taken out after molding. The sample was placed in an incubator with a temperature of 37°C and a humidity of 100% for curing for 72h to obtain magnesium phosphate cement (MPC).

[0047] Step 3: Preparation of magnesium phosphate cement / nanozyme composite material MPC / bCeO (MPbC)

[0048] CaHPO4 (0.01 mol, 1.33 g), NaH2PO4 (0.01 mol, 1.17 g) and MgO powder (0.005 mol, 0.2 g) were mixed, and the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1. Hydroxyapatite (HA, Ca5(PO4)3(OH)) (5.38×10-4 mol, 0.27g) are mixed evenly, the mass percentage of hydroxyapatite (HA) to the total mass of CaHPO4, NaH2PO4 and MgO is 10wt%, the above mixed powder is mixed evenly with CeO-2 (0.297g), the mass percentage of CeO-2 to the total mass of CaHPO4, NaH2PO4, MgO and hydroxyapatite is 10wt%, deionized water is added to make the liquid-solid ratio 200μL / g (add 0.65ml of water), fully blended and filled into a polytetrafluoroethylene mold, and taken out after molding. The sample is placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain a magnesium phosphate bone cement / nanozyme composite material, abbreviated as MPbC-1.

[0049] CaHPO4 (0.01 mol, 1.33 g), NaH2PO4 (0.01 mol, 1.17 g) and MgO powder (0.00489 mol, 0.1956 g) were mixed, and the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1. Hydroxyapatite (HA) (5.38 × 10 - 4 mol, 0.27g) are mixed evenly, the mass percentage of hydroxyapatite (HA) to the total mass of CaHPO4, NaH2PO4 and MgO is 10wt%, the above mixed powder is mixed evenly with CeO-2 (0.60g), the mass percentage of CeO-2 to the total mass of CaHPO4, NaH2PO4, MgO and hydroxyapatite is 20wt%, deionized water is added to make the liquid-solid ratio 200μL / g (add 0.71ml of water), fully blended and filled into a polytetrafluoroethylene mold, and taken out after molding. The sample is placed in an incubator with a temperature of 37°C and 100% humidity for curing for 72h to obtain a magnesium phosphate bone cement / nanozyme composite material, abbreviated as MPbC-2.

[0050] CaHPO4 (0.01 mol, 1.33 g), NaH2PO4 (0.01 mol, 1.17 g) and MgO powder (0.005 mol, 0.2 g) were mixed, and the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1. Hydroxyapatite (HA) (5.38 × 10 -4mol, 0.27g) are mixed evenly, the mass of hydroxyapatite (HA) accounts for 10wt% of the total mass of CaHPO4, NaH2PO4 and MgO, the above mixed powder is mixed evenly with CeO-2 (0.9g), the mass of CeO-2 accounts for 30wt% of the total mass of CaHPO4, NaH2PO4, MgO and hydroxyapatite, deionized water is added to make the liquid-solid ratio 200μL / g (add 0.77ml of water), fully blended and filled into a polytetrafluoroethylene mold, and taken out after molding. The sample is placed in an incubator with a temperature of 37°C and 100% humidity for curing for 72h to obtain a magnesium phosphate bone cement / nanozyme composite material, abbreviated as MPbC-3.

[0051] Table 2 MPC / bCeO (MPbC) sample grouping

[0052]

[0053] 1. Characterization of the physical and chemical properties of oxygen vacancy cerium oxide (bCeO)

[0054] Scanning electron microscopy (SEM, S 4800, Hitachi, Japan) was used to observe the microstructure and particle size of bCeO.

[0055] The crystal structure of bCeO was analyzed using an X-ray diffractometer (XRD, D / max2550VB / PC, Japan) (angle: 10°-80°, scanning speed: 5° / min).

[0056] The valence band of bCeO was analyzed using an X-ray photoelectron spectroscopy (XPS, Thermo Scientific K Alpha, USA).

[0057] The bandgap of bCeO was analyzed using an ultraviolet-visible-near-infrared spectrometer (UV-vis-NIR, Lambda 950, USA).

[0058] A standard three-electrode system (Pt counter electrode, Ag / AgCl reference electrode, and GCE working electrode) was used in an electrochemical workstation (PARSTAT2273, USA) at 1.5 W / cm 2 The electrochemical properties of the samples were measured under US conditions. The GCE working electrode was prepared by coating the powder dispersion droplets on the conductive glass surface and drying it. Electrochemical impedance spectroscopy (EIS) was performed in the open circuit voltage range of 0.01 to 1 V in Na2SO4 electrolyte (0.1 M).

[0059] 2. Characterization of the sonodynamic properties of magnesium phosphate bone cement / nanozyme composites

[0060] The bandgap of bCeO was analyzed using an ultraviolet-visible near-infrared spectrometer (UV-vis-NIR, Lambda 950, USA). Rhodamine B (RhB, 10 mg / L), methylene blue (MB, 5 mg / L) and 1,3-diphenylisobenzofuran (DPBF, 5 mg / L) were used to detect the total ROS, ·OH and ·O2 generated by the samples, respectively. - .

[0061] 10 mg of sample was immersed in 10 mL of solution and irradiated with US (1 MHz, 1.5 W / cm 2 ), react for 5 min, centrifuge and take the supernatant, measure the absorbance of the supernatant to obtain the ROS generation efficiency. 2 ) 0, 2, 4, 6, 8, and 10 min later, the absorbance of the supernatant was measured. 2 ) and the absorbance of the supernatant was measured after 5 min of US irradiation.

[0062] 3. Characterization of enzyme activity of magnesium phosphate bone cement / nanozyme composites

[0063] POD enzyme activity: MB (5 mg / L) was used to detect the POD enzyme activity of bCeO and MPbC samples.

[0064] 10 mg of sample was immersed in 10 mL MB solution containing 10 mM H2O2, the pH of the solution was 5.5, after 10 min of reaction, the supernatant was centrifuged and the absorbance of the supernatant was measured. The pH of the solution was 5.5, and the absorbance of the supernatant was measured at different powers (1 MHz, 0, 0.3, 0.5, 0.8, 1, 1.5 W / cm 2 ) under US irradiation, react for 5 min, and measure the absorbance of the supernatant. Under different pH conditions (4.5, 5.5, 6.5, 7.4), react for 10 min, and measure the absorbance of the supernatant.

[0065] CAT enzyme activity: The dissolved oxygen content in the solution was detected by a dissolved oxygen meter (JPB-607A, China) to characterize the CAT enzyme activity of bCeO and MPbC samples.

[0066] 50 mg of the sample was immersed in 50 mL of PBS solution containing 10 mM H2O2, and the pH of the solution was 7.4. The dissolved oxygen content (mg / L) was measured using a dissolved oxygen meter at different times (every 5 min within 1 h). The pH of the solution was 7.4, and the dissolved oxygen content (mg / L) was measured at different powers (1 MHz, 0, 0.3, 0.5, 0.8, 1, 1.5 W / cm 2) and tested the dissolved oxygen content under different pH conditions (4.5, 5.5, 6.5, 7.4).

[0067] 4. In vitro cell experiments of magnesium phosphate bone cement / nanozyme composites

[0068] Rat bone marrow mesenchymal stem cells (rBMSCs) were purchased from the Shanghai Cell Bank of the Chinese Academy of Sciences and cultured in a medium (α-MEM, TBD, USA) supplemented with 10% fetal bovine serum (FBS, Gibco, USA) and 1% penicillin / streptomycin (P / S, TBD, China) at 37°C in an atmosphere of 5% CO2. The medium was changed every 3 days, and rBMSCs of passages 3 to 5 were used for cell experiments.

[0069] Cytotoxicity of magnesium phosphate cement / nanozyme composites:

[0070] The MPbC-3 samples were ground into powder and sterilized by ultraviolet irradiation. The complete culture medium extracts with concentrations of 100, 200, 300, 400, and 500 μg / mL were prepared. The cytotoxicity of the samples was evaluated using a cell counting kit (CCK-8, Beyotime, China). Different concentrations of samples were added to the culture medium, and rBMSCs (density of 2×10 4 / well) and samples were cultured in a 96-well plate for 24 h, CCK-8 solution (100 μL) was added to the culture medium, and after incubation for 1 h, the absorbance (OD value) of the culture medium was detected at a wavelength of 450 nm using a microplate reader (SpectraMax iD5, molecular Devices, Australia).

[0071] Cell proliferation of magnesium phosphate cement / nanozyme composites:

[0072] The magnesium phosphate cement / nanozyme composite was sterilized by ultraviolet irradiation. The samples were divided into 2 groups: (1) MPC+US; (2) MPbC-3+US. CCK-8 was used to evaluate the proliferation of cells on the samples. rBMSC (density 2×10 4 / well) and samples were cultured in 96-well plates for different time periods (1d, 3d, 7d). After 24h of culture, the cells were exposed to 1MHz, 0.5W / cm 2 rBMSCs were irradiated with US (twice a day, 10 seconds each time). Subsequently, CCK-8 solution (100 μL) was added to the culture medium. After incubation for 1 hour, the absorbance (OD value) of the culture medium was measured at a wavelength of 450 nm using an ELISA reader (SpectraMax iD5, molecular Devices, Australia).

[0073] 5. In vitro antibacterial experiment of magnesium phosphate bone cement / nanozyme composite material

[0074] Staphylococcus aureus (S. aureus, ATCC 29213) and Escherichia coli (E. coli, ATCC 25922) were used to test the antibacterial effect of the samples in vitro. S. aureus and E. coli were cultured in tryptone soy broth (TSB) and lysogeny broth (LB) medium, respectively. They were cultured in a 37°C incubator for 12 hours before use.

[0075] The samples were divided into 4 groups: MPC, MPbC-3, MPC+US, and MPbC-3+US. The antibacterial ratio was determined by colony counting method.

[0076] (1) MPC: Before the experiment, the samples were sterilized by ultraviolet irradiation for 12 h. 6 The bacterial suspension (1 mL) with CFU / mL was co-cultured with the sample MPC (500 ug / mL) in a 24-well plate (37°C, 6 h). 100 μmol, 2 mM H2O2 was added. After 20 min of treatment, the bacterial suspension on the surface of all samples was collected by ultrasound, and the bacterial suspension was diluted 10 times, 100 μL was spread on the nutrient agar plate, and the bacterial colonies formed after incubation at 37°C for 16 h were recorded and counted using a digital camera.

[0077] (2) MPbC-3: Before the experiment, the samples were sterilized by ultraviolet irradiation for 12 h. 6 CFU / mL bacterial suspension (1mL) was co-cultured with sample MPbC-3 (500ug / mL) in a 24-well plate (37°C, 6h). 100μmol, 2mM H2O2 was added. After 20min of treatment, the bacterial suspension on the surface of all samples was collected by ultrasound, and the bacterial suspension was diluted 10 times, 100μL was spread on the nutrient agar plate, and a digital camera was used to record and count the bacterial colonies formed after incubation at 37°C for 16h.

[0078] (3) MPC+US: Before the experiment, the samples were sterilized by ultraviolet irradiation for 12 h. 6 CFU / mL bacterial suspension (1 mL) and sample MPC (500 ug / mL) were co-cultured in a 24-well plate (37°C, 6 h). 100 μmol, 2 mM H2O2 was added. The treatment lasted for 20 min and the cells were treated with an ultrasonic therapy device (1.5 W / cm 2 The bacterial suspension on the surface of all samples was collected by ultrasound, and the bacterial suspension was diluted 10 times, 100 μL was spread on the nutrient agar plate, and the bacterial colonies formed after incubation at 37°C for 16 h were recorded and counted using a digital camera.

[0079] (4) MPbC-3+US: Before the experiment, the samples were sterilized by ultraviolet irradiation for 12 h. 6 CFU / mL bacterial suspension (1 mL) and sample MPbC-3 (500 ug / mL) were co-cultured in a 24-well plate (37°C, 6 h). 100 μmol, 2 mM H2O2 was added. The treatment lasted for 20 min and the cells were treated with an ultrasonic therapy device (1.5 W / cm 2 The bacterial suspension on the surface of all samples was collected by ultrasound, and the bacterial suspension was diluted 10 times, 100 μL was spread on the nutrient agar plate, and the bacterial colonies formed after incubation at 37°C for 16 h were recorded and counted using a digital camera.

[0080] The antibacterial rate calculation formula is as follows:

[0081]

[0082] Where C and S are the colony numbers of the control group and the sample group, respectively.

[0083] 6. Results and Discussion

[0084] Figure 1 The following is a schematic diagram of the SEM images of bCeO at different magnifications. The reducing agent NaBH4 can produce hydrogen under thermal decomposition, capturing the lattice oxygen in CeO to produce oxygen vacancies. From the SEM images, it can be seen that oxygen vacancies will not change the particle size of CeO. The particle sizes of CeO, CeO-1, CeO-2, and CeO-3 are all around 50nm.

[0085] Figure 2 The XRD spectrum of bCeO is shown in Figure 1. The XRD spectrum shows that there is no significant difference in the diffraction peaks of CeO, CeO-1, CeO-2, and CeO-3, indicating that thermal reduction does not significantly change the crystal structure of CeO.

[0086] Figure 3 The figure is a schematic diagram of the sonodynamic performance of bCeO. The sonodynamic performance of bCeO was evaluated by the ability to generate ROS to degrade Rhodamine B (RhB) by triggering the sonodynamics of bCeO with US. Among the samples CeO, CeO-1, CeO-2, and CeO-3, CeO-2 has the best sonodynamic performance, indicating that appropriate oxygen vacancies can enhance the sonodynamic performance.

[0087] Figure 4The figure is the bandgap width of bCeO, the valence band XPS spectrum of CeO-2, and the schematic diagram of electrochemical impedance. Among them, a is the schematic diagram of the bandgap width of bCeO. It can be seen from the figure that the bandgap width of CeO-2 (2.85eV) is significantly reduced compared with CeO (2.95eV). b is the schematic diagram of the valence band XPS spectrum of CeO-2. It can be seen from the figure that the valence band of CeO-2 is 1.36eV. c is the schematic diagram of electrochemical impedance. It can be seen from the figure that oxygen vacancies reduce the impedance of CeO-2. The reduced impedance indicates that it is easier to promote the separation of electrons and holes, thereby enhancing the acoustic power.

[0088] Figure 5 Figure 1 is a schematic diagram of the POD enzyme activity and CAT enzyme activity data of bCeO. Among them, a is a schematic diagram of the POD enzyme activity results of bCeO; b is a schematic diagram of the CAT enzyme activity results of bCeO. It can be seen from the figure that compared with CeO, the POD and CAT enzyme activities of oxygen vacancy CeO-2 are enhanced, indicating that appropriate oxygen vacancies can enhance the activity of nanozymes.

[0089] Figure 6 Figure 1 is a schematic diagram of the acoustic dynamic performance results of different samples. Among them, a is a schematic diagram of the acoustic dynamic performance results of different samples, b is a schematic diagram of the relationship between the acoustic dynamics of MPbC-3 and time, and c is a schematic diagram of the relationship between the acoustic dynamics of MPbC-3 and O2 - a is a schematic diagram of the relationship between MPbC-3 acoustic dynamics and time, and d is a schematic diagram of the relationship between MPbC-3 acoustic dynamics and US power. Figure 6 Figure a shows that MPbC-3 has the best sonodynamic performance, indicating that its sonodynamic performance gradually increases with the increase of CeO-2 content. Figure 6 Figures b and c show that MPbC-3 can continuously produce ·OH and ·O2 under the action of US. - And many other ROS. Figure 6 The middle d indicates that US≤0.5W / cm 2 When US>0.5W / cm 2 When the US power increases, MPbC-3 is sonodynamically excited, and the excitation gradually increases with the increase of US power, and the ROS yield increases. The above results show that MPbC-3 can produce a large amount of ·OH and ·O2 - This is because its CeO-2 content is the highest, and the acoustic dynamic performance is improved accordingly, and the acoustic dynamics of MPbC-3 increases with the increase of US power.

[0090] Figure 7Schematic diagram of the results of POD enzyme activity and CAT enzyme activity of different samples. Among them, a is a schematic diagram of the results of POD enzyme activity of different samples, b is a schematic diagram of the results of POD enzyme activity of MPbC-3 at different pH, c is a schematic diagram of the results of POD enzyme activity of MPbC-3 at different powers, d is a schematic diagram of the results of CAT enzyme activity of different samples, e is a schematic diagram of the results of CAT enzyme activity of MPbC-3 at different pH, and f is a schematic diagram of the results of CAT enzyme activity of MPbC-3 at different powers. Figure 7 Figure (a) shows that MPbC-3 has the best POD enzyme activity compared with other samples, which is due to the highest CeO-2 content in MPbC-3. Figure 7 Figure b shows that as the pH decreases, the POD enzyme activity of MPbC-3 increases, indicating that the POD enzyme activity is better under acidic conditions. Figure 7 Figure c shows that as the US power increases, the POD enzyme activity of MPbC-3 gradually increases. This is because US ≤ 0.5 W / cm 2 When US>0.5W / cm 2 When the sound is stimulated, a large amount of ·OH is produced together with the POD enzyme activity. Figure 7 Figure d shows that MPbC-3 has the best CAT enzyme activity compared with other samples, which is due to the highest CeO-2 content in MPbC-3. Figure 7 Figure e shows that the CAT enzyme activity of MPbC-3 increases with increasing pH, indicating that the CAT enzyme activity is better under neutral conditions. Figure 7 f indicates that US≤0.5W / cm 2 When US>0.5W / cm 2 When the sound is stimulated, the oxygen produced by the CAT enzyme activity is consumed, so the dissolved oxygen content decreases.

[0091] Figure 8 The diagrams are the results of cytotoxicity and cell proliferation of different samples. a is the results of cytotoxicity of different samples, and b is the results of proliferation of cells and samples after 1, 3 and 7 days of culture. Figure 8 Figure (a) shows that with increasing concentrations of MPC and MPbC-3, both samples had no cytotoxicity. Figure 8 Figure b shows that cell proliferation increases with the increase of cell culture time, indicating that both materials have excellent biocompatibility. The cell proliferation of MPbC-3 is better than that of MPC, which is because cerium oxide improves the bioactivity of MPbC-3, thereby promoting cell proliferation.

[0092] Fig. 9 The figure is a schematic diagram of colony photos and antibacterial rate results after culturing different samples and different conditions. Among them, a is a schematic diagram of colony photos against S. aureus after culturing different samples and different conditions, b is a schematic diagram of colony photos against E. coli after culturing different samples and different conditions, c is a schematic diagram of antibacterial rate results against S. aureus, and d is a schematic diagram of antibacterial rate results against E. coli. Fig. 9 The antibacterial effects of a and b show that MPC and MPbC-3 alone have no antibacterial properties. Under the action of US, the antibacterial effect of MPbC-3 is significantly better than that of MPC. This is because MPbC-3 contains bCeO, which enhances the sonodynamic properties and can generate a large amount of ROS to enhance the bactericidal function. Fig. 9 As shown in Figures c and d, the antibacterial rates were 93.4%±1.8% (S. aureus) and 98.4%±2.1% (E. coli), respectively.

[0093] The present invention firstly prepares CeO-2 with an appropriate amount of oxygen vacancies by thermal reduction with NaBH4, and reduces its bandgap width by oxygen vacancy defects; oxygen vacancies can serve as charge capture centers and adsorption sites, promote the separation of electron holes, make it easier to be excited by US to generate acoustic power, and improve its POD and CAT enzyme activities. Then, CeO-2 is blended with the prepared magnesium phosphate cement (MPC) to prepare the composite material MPbC-3. Compared with MPC, MPbC-3 has acoustic power and enzyme activity, is non-cytotoxic, has biocompatibility, and can promote osteoblast proliferation. In the bacterial infection microenvironment (pH = 5.5), under US triggering, acoustic power and enzyme-like activity synergistically produce a large amount of ROS, thereby achieving effective sterilization and removal of biofilm. In summary, the present invention prepares an antibacterial bone repair material with acoustic power and enzyme activity, which has antibacterial function and biological activity to promote osteoblast proliferation, and is expected to be used for the treatment and repair of deep infected tissues.

[0094] The results showed that oxygen vacancies provided the sonodynamic properties of CeO-2 and enhanced its POD and CAT enzyme activities. CeO-2 increased the bioactivity of MPbC-3 and promoted cell proliferation. Under US irradiation, MPbC-3 combined sonodynamic and enzyme activities to produce multiple ROS and synergistically kill bacteria / clear biofilm. Therefore, MPbC-3 has potential application prospects in the treatment of infected bone tissue.

[0095] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A magnesium phosphate bone cement / nanozyme composite material, characterized in that: The invention is prepared from CaHPO4, NaH2PO4, MgO powder, hydroxyapatite and oxygen vacancy cerium oxide, wherein the molar ratio of CaHPO4, NaH2PO4 and MgO is 1-4:1-4:1, the mass percentage of hydroxyapatite to the total mass of CaHPO4, NaH2PO4 and MgO is 5-20wt%, and the mass percentage of oxygen vacancy cerium oxide to the total mass of CaHPO4, NaH2PO4, MgO and hydroxyapatite is 5-40wt%.

2. The magnesium phosphate bone cement / nanozyme composite material according to claim 1, characterized in that: The oxygen vacancy cerium oxide is prepared from cerium oxide and sodium borohydride in a molar ratio of 1:0.5-2.

3. A method for preparing the magnesium phosphate bone cement / nanozyme composite material according to claim 1 or 2, characterized in that: The following steps are involved: Mix CaHPO4, NaH2PO4 and MgO powders in a molar ratio of 1 to 4:1 to 4:1, add hydroxyapatite and mix evenly, the mass percentage of hydroxyapatite to the total mass of CaHPO4, NaH2PO4 and MgO is 5 to 20wt%, mix the above mixed powder evenly with oxygen vacancy cerium oxide, the mass percentage of oxygen vacancy cerium oxide to the total mass of CaHPO4, NaH2PO4, MgO and hydroxyapatite is 5 to 40wt%, add deionized water so that the liquid-solid ratio is 170 to 210 μL / g, fully blend, fill into a mold for molding, and solidify to obtain the magnesium phosphate bone cement / nanozyme composite material.

4. The method for preparing the magnesium phosphate bone cement / nanozyme composite material according to claim 3, characterized in that: The curing conditions are as follows: the sample is placed in an incubator at a temperature of 37° C. and a humidity of 100% for curing for 1 to 72 hours.

5. The method for preparing the magnesium phosphate bone cement / nanozyme composite material according to claim 3, characterized in that: The preparation method of the oxygen vacancy cerium oxide comprises the following steps: Cerium oxide and sodium borohydride are mixed in a molar ratio of 1:0.5-2, calcined for 0.5-2h in an argon atmosphere at a temperature of 350-500°C, washed, and dried to obtain the oxygen vacancy cerium oxide.

6. The method for preparing the magnesium phosphate bone cement / nanozyme composite material according to claim 5, characterized in that: The washing conditions are: washing with water and ethanol in sequence.

7. The method for preparing the magnesium phosphate bone cement / nanozyme composite material according to claim 5, characterized in that: The drying conditions are as follows: drying at 60° C. for 1 h.

8. The method for preparing the magnesium phosphate bone cement / nanozyme composite material according to claim 3, characterized in that: The preparation method of the MgO powder comprises the following steps: The basic magnesium carbonate is calcined at a temperature of 750 to 900° C. for 0.5 to 2 hours for dehydration, and then calcined at a temperature of 1450 to 1600° C. for 0.5 to 3 hours to obtain a magnesium oxide block, which is then ground to obtain the MgO powder.

9. Use of the magnesium phosphate bone cement / nanozyme composite material according to claim 1 or 2 in preparing a bone repair scaffold.

10. Use of the magnesium phosphate bone cement / nanozyme composite material according to claim 1 or 2 in the preparation of bone repair materials or bone transplant materials.